Beauty shop politics: African American women's activism in the beauty industry - Gill, Tiffany M. (Urbana, 2010)
"Beauty Shop Politics Shows how black beauticians in the Jim Crow era parlayed their economic independence and access to a public community space into platforms for activism. This book argues that the beauty industry played a crucial role in the creation of the modern black female identity. Full description."